Molecular genetic analysis of two large kindreds with intracranial aneurysms demonstrates linkage to 11q24-25 and 14q23-31 - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Background and Purpose - Both environmental and genetic factors contribute to the formation, growth, and rupture of intracranial aneurysms (IAs). To search for IA susceptibility genes, we took an outlier approach, using parametric genome-wide linkage analysis in extended IA kindreds in which IA is inherited as a simple Mendelian trait. We hereby present the molecular genetic analysis of 2 such families. Methods - For genome-wide linkage analysis, we used a 2-stage approach. First, using gene chips in affected-only analysis, we identified genomic regions that provide maximum theoretical logarithm of odds (lod) scores. Next, to confirm or exclude these candidate loci, we genotyped all available family members, both affected and unaffected, using polymorphic microsatellite markers located within these regions. Results - We obtained significant lod scores of 4.3 and 3.00 for linkage to chromosomes 11q24-25 and 14q23-31, respectively. Conclusions - Molecular genetic analysis of 2 large IA kindreds confirms linkage to chromosome 11q and 14q, which were suggested to contain IA susceptibility genes in a previous study of Japanese sib pairs. Independent identification of these 2 loci strongly suggests that IA susceptibility genes lie within these regions. While demonstrating the genetic heterogeneity of IA, these results are also an important step toward cloning IA genes and ultimately understanding its pathophysiology.
Keywords: aneurysm; genetics; ABDOMINAL AORTIC-ANEURYSMS; GENOME-WIDE LINKAGE; SUBARACHNOID HEMORRHAGE; CEREBRAL ANEURYSMS; CHROMOSOME 19Q13.3; CANDIDATE GENES; FAMILIES; LOCUS; CONFIRMATION; HYPERTENSION